How to lead when you're not in charge eaudiobook Leveraging influence when you lack authority. - Scroggins, Clay (Zondervan, 2017)
Are you hungry to help others through leadership but don't feel like you have the authority? "If you're ready to lead right where you are, this book can show you how to start." - Dave Ramsey, #1 National bestselling author and host of The Ramsey Show. One of the greatest myths of leadership is that you must be in charge in order to lead. Great leaders don't buy it. Great leaders—whether they have the official authority or not—learn how to be an influential presence wherever they are. In How to Lead When You're Not in Charge, author and pastor Clay Scroggins explains the nature of leadership and what's needed to be a great leader—even when you answer to someone else. Drawing from biblical principles and his experience as the lead pastor of Buckhead Church in Atlanta, Georgia, Clay will help you nurture your vision and cultivate influence with integrity and confidence, even when you lack authority in your organization or ministry. In this book, Clay will walk you through the challenge of leadership and the four basic behaviors all great leaders have and how to cultivate them: Leading yourself Choosing positivity Thinking critically Rejecting passivity With practical wisdom and humor, Clay Scroggins will help you free yourself to become the great leader you want to be so you can make a difference. Even when you're not in charge.